PENGARUH ANALISIS JABATAN DAN PENGEMBANGAN KARIR MELALUI KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN TEBO - Arna Suryani; Rini Susanti (Universitas Batanghari, 2016)
The purpose of this study is to determine the effect of Job Analysis and Competency Career Development Through Employee Performance Against Religious Affairs Office of Tebowitha population of31personnel.. The results showed, in the school environment to support Based on the research results, TCRvariablejob analysis(X1) of 1844, career development(X2) amounted to1,210, competence(Y) of 1847, andthe performance ofemployees(Z) of 1,348. Effect ofX1to Yat0.682, X2to Yat0.173, ANOVAvalueX1, X2to Yat27.746. Meanwhile, theinfluenceof theZamounted to0.701X1, X2toZof0.280, ANOVAvaluesX1andX2 toZat81.229. Meanwhile, the effect ofjob analysisand career developmenttogetherwiththe competenceof38.4859%.